Treatment in locally advanced rectal cancer: a machine learning bibliometric analysis. (October 2021) - De Felice, Francesca; Crocetti, Daniele; Petrucciani, Niccolò; Belgioia, Liliana; Sapienza, Paolo; Bulzonetti, Nadia; Marampon, Francesco; Musio, Daniela; Tombolini, Vincenzo
A bibliometric analysis was performed using a machine learning bibliometric methodology in order to evaluate the research trends in locally advanced rectal cancer treatment between 2000 and 2020. Information regarding publication outputs, countries, institutions, journals, keywords, funding, and citation counts was retrieved from Scopus database. During the search process, a total of 2370 publications were identified. The vast majority of papers originated from the United States of America, reflecting also its research drive in the collaboration network. Neoadjuvant treatment was the topic most studied in the highly cited studies. New keywords, including neoadjuvant chemotherapy, multiparametric magnetic resonance imaging, circulating tumor DNA, and genetic heterogeneity, appeared in the last 2 years. The quantity of publications on locally advanced rectal cancer treatment since 2000 showed an evolving research field. The 'new' keywords explain where research is presently heading.